Analysis of Work Environment, Compensation, Training, and Work Discipline on Employee Loyalty Mediated by Job Performance at Badan Pusat Statistik Lamongan Using Partial Least Square (PLS)-Structural Equation Modeling (SEM) - Sholihah, Zumrotus; Muhtarom, Abid; Hamzah, Muhammad Imron; Lazuardi, Yanuar; Sulaeman, Moh. Muklis (Indonesian Journal of Contemporary Multidisciplinary Research, 2025)
This research aims to determine the influence of the Work Environment, Compensation, Training and Work Discipline on Employee Loyalty mediated by Work Performance at the Lamongan Central Statistics Agency. This research uses descriptive quantitative research. Data collection for this thesis was taken through a questionnaire. The respondents in this research were employees and partners of the Lamongan Central Statistics Agency in November and December 2024. The research results state that the influence of employee loyalty has a positive and significant effect on employee loyalty. Compensation has a negative and insignificant effect on employee loyalty. Training has a positive but not significant effect on employee loyalty. Work discipline has a positive and significant effect on employee loyalty. The work environment has a positive but not significant effect on work performance. Compensation has a positive and significant effect on work performance. Training has no positive and insignificant effect on work performance. Work discipline has a positive and significant effect on work performance. Employee loyalty has a positive and significant effect on work performance. Work performance is able to mediate between the independent variable and the dependent variable.